Perfil de voláteis de variedades melhoradas de pimentas Capsicum chinenses utilizando técnicas de HS-SPME, CG-EM e CG-Olfatometria - Almeida, Áfia Suely Santos da Silva (2015)
There is an interest in scientific research related to the different aspects of peppers crops, due to the importance of variability between different species and cultivars, their sensory attributes such as taste, scent, pungency, the growing consumption and its chemical composition. Therefore, this study aimed to characterize the volatile profile of five pepper varieties of the genus Capsicum Chinense with different pugency levels and scents and specific objectives: to analyze the volatile profile of Orange Biquinho peppers, Salmon Biquinho pepper, Red Biquinho, Orange and Red Habanero; to identify odorous compounds of the Orange Biquinho variety. Through the Osme olfactometry technique and compare the five varieties of peppers related to the most important odorous compounds. The samples, which were obtained from the Germplasm Bank of Embrapa Vegetables (Brasília, Brazil), were submitted to Headspace Solid-Phase Microextraction technique (HS-SPME) to characterize the volatile profile. The identification of active compounds for peppers scent was obtained from the use of gas chromatography-olfactometry technique (GC-Osme), where 80 peaks were detected and among these, 14 exhibited high and medium intensity odorant. Among the five varieties of peppers studied, it was possible the identification of 95 compounds, with the esters (55%) main chemical class, followed terpenes (23%), hydrocarbon (11%), alcohol (10%) and ketones (1%) and acid (0.35%). The volatile profile of five varieties of Capsicum Chinense studied peppers showed no differences in the chromatogram area related chemical classes found, except the Habanero red pepper, that showed a significant difference from the chromatogram area for the chemical class of identified alcohols. The Habanero peppers presented quantitatively richer volatile profile than the varieties of Biquinho peppers, which had very similar volatile profile of each other. The red Habanero variety presented itself richer in pepper odor compounds than its orange variety, characterized by more compounds of floral scent.